PBO composite aerogel with double-cross-linked network structure and preparation method of PBO composite aerogel
By constructing a PBO composite gas gel with dual -link network structure, polybenzenzene and nanozine fiber are used to form a network of networks, and hydrophobic coating on the surface solves the problem of poor interaction between PBO nano fibers and realizes the realization. The stability and multifunctional properties of gas gel are improved.
Patent Information
- Application Number
- CN202411636201.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The interaction between PBO nanofibers is poor and it is difficult to form stable aerogels, which limits its wider application.
By using polybenzene -phenzide molecular chains to form a network structure with PBO nano -fiber, and sedify hydrophobic coating on the surface of nano composite gas gel to build a dual -link network structure PBO composite gas gel.
It improves the overall mechanical performance, thermal stability and thermal insulation performance of the nano composite gas gel, and gives them ultra -hydrophobic properties, and expands the application prospects of PBO fiber.
Smart Images

Figure CN119371713A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanofiber aerogels, and in particular to a double-crosslinked network structure PBO composite aerogel and a preparation method thereof. Background Art
[0002] Poly(p-phenylene benzobisoxazole) (PBO) fibers have outstanding thermal decomposition temperature (650°C), extremely high tensile strength (5.8 GPa) and excellent flame retardant properties (limiting oxygen index of 68), and are known as the super fibers of the 21st century. Therefore, PBO nanofibers derived from PBO fibers have broad application prospects in aerospace, electronic information, and 5G communications. However, the interaction between PBO nanofibers is poor, and it is difficult to form stable aerogels, which limits its wider application. At present, there are few reports on the preparation of PBO nano aerogels. How to improve the interaction between PBO nanofibers and improve the stability of the nanofiber network is still a huge challenge. Summary of the invention
[0003] The purpose of the present invention is to provide a double cross-linked network structure PBO composite aerogel and a preparation method thereof, so as to solve the technical problem in the above-mentioned prior art that it is difficult to form a stable aerogel due to poor interaction between PBO nanofibers. The double cross-linked network structure PBO composite aerogel prepared by the present invention has excellent mechanical properties, hydrophobic properties and flame retardant properties, so that PBO fibers have broader application prospects.
[0004] To achieve the above object, the present invention provides the following solutions:
[0005] One of the technical solutions of the present invention: a double cross-linked network structure PBO composite aerogel, the double cross-linked network structure PBO composite aerogel comprising: a nano composite aerogel with a double cross-linked network structure constructed by polybenzoxazine and PBO nanofibers, and a hydrophobic coating deposited on the surface of the nano composite aerogel; the hydrophobic coating comprises fluorocarbon resin and fumed silica.
[0006] Benzoxazine can be polymerized under acidic conditions to form polybenzoxazine. The present invention uses polybenzoxazine molecular chains and PBO nanofibers to form an interpenetrating network structure to enhance the stability of the aerogel. In addition, the main chain and side chain of the polybenzoxazine molecular chain contain a large number of hydroxyl groups and benzene rings, which form strong hydrogen bonds and other non-covalent interactions with the PBO nanofibers, thereby overcoming the technical problem of weak interactions between PBO nanofibers and making it possible for PBO fibers to form stable aerogels. The present invention not only improves the overall mechanical properties of the nanocomposite aerogel by constructing a double cross-linked network structure, but also improves the thermal stability and thermal insulation properties of the aerogel; on this basis, a hydrophobic coating is deposited on the surface of the nanocomposite aerogel, and the surface free energy of the aerogel surface is reduced and the surface roughness is increased by regulating and controlling the fluorocarbon resin and the fumed silica, so that the coating can form a more uniform super-hydrophobic structure, thereby having super-hydrophobic properties. Therefore, the double cross-linked network structure PBO composite aerogel provided by the present invention has excellent mechanical properties, super-hydrophobic properties, flame retardant properties and low thermal conductivity.
[0007] Preferably, the raw materials of the double cross-linked network structure PBO composite aerogel include, by weight: 10 to 50 parts of PBO fibers, 100 to 300 parts of methanesulfonic acid, 100 to 300 parts of trifluoroacetic acid, 50 to 100 parts of benzoxazine, 2 to 5 parts of anhydrous sodium sulfate, 80 to 140 parts of fluorocarbon resin and 1 to 4 parts of fumed silica.
[0008] Preferably, the benzoxazine is a diamine / phenol type benzoxazine.
[0009] Preferably, the method for preparing the nanocomposite aerogel comprises the following steps:
[0010] The PBO fibers are dispersed in a mixed acid solution consisting of methanesulfonic acid and trifluoroacetic acid to obtain a PBO nanofiber dispersion;
[0011] Adding benzoxazine and anhydrous sodium sulfate into the PBO nanofiber dispersion to prepare a polybenzoxazine / PBO nanocomposite acid sol;
[0012] The polybenzoxazine / PBO nanocomposite acid gel is subjected to solvent exchange in a solvent and then freeze-dried to obtain the nanocomposite aerogel.
[0013] The invention firstly uses a mixed acid solution of trifluoroacetic acid and methanesulfonic acid to prepare a PBO nanofiber dispersion liquid, then adds benzoxazine and anhydrous sodium sulfate into the PBO nanofiber dispersion liquid, uses trifluoroacetic acid and methanesulfonic acid as acid catalysts to promote the ring-opening polymerization of benzoxazine to form polybenzoxazine, and uses anhydrous sodium sulfate to modify the PBO nanofibers. Sulfate ions can reduce the electrostatic repulsion between the PBO nanofibers and improve the π-π interaction of the PBO nanofibers, so that the polybenzoxazine and the PBO nanofibers form an interpenetrating network structure, and a stable nano composite aerogel is obtained.
[0014] Because water will form hydrogen bonds with hydrogen ions in the acid, causing the effect of the acid on the PBO fiber to be reduced, so that stable PBO nanofibers cannot be formed, the reaction system requires an anhydrous environment. Based on this, the present invention uses anhydrous sodium sulfate as a modifier.
[0015] The present invention uses a mixed acid solution of trifluoroacetic acid and methanesulfonic acid to prepare the PBO nanofiber dispersion because the mixed acid solution of trifluoroacetic acid and methanesulfonic acid has a better dispersion effect on PBO fibers. In addition, benzoxazine can also be polymerized in trifluoroacetic acid and methanesulfonic acid, which is beneficial to the preparation of nanocomposite aerogels.
[0016] Preferably, the mass fraction of the PBO fiber is 20 to 50 parts.
[0017] Preferably, the PBO fiber has a length of 10 to 20 cm and a diameter of 10 to 15 μm.
[0018] Preferably, the mass fraction of the methanesulfonic acid is 100 to 200 parts.
[0019] Preferably, the mass fraction of the trifluoroacetic acid is 100 to 200 parts.
[0020] Preferably, the mass fraction of the benzoxazine is 70 to 100 parts.
[0021] Preferably, the purity of the benzoxazine is ≥ 95%.
[0022] Preferably, the mass fraction of the anhydrous sodium sulfate is 3 to 5 parts.
[0023] Preferably, the purity of the anhydrous sodium sulfate is ≥95%.
[0024] Preferably, the mass fraction of the fluorocarbon resin is 80 to 120 parts.
[0025] Preferably, the mass fraction of fumed silica is 1 to 3 parts.
[0026] The present invention limits the amount of each raw material so that each component cooperates with each other to obtain the best product performance. The amount of each raw material is limited to maintain its specific performance and meet the requirements of process conditions and application fields. Exceeding the dosage range may lead to problems such as performance degradation, increased processing difficulty and safety hazards. The mutual cooperation of the amounts of the raw materials determines the overall performance and stability of the aerogel. Therefore, when preparing aerogels, it is necessary to strictly control the amount of raw materials and the mutual cooperation to obtain the best product performance. For example, if the amount of fumed silica in the hydrophobic coating is too much, the viscosity of the fluorocarbon resin / fumed silica mixture will be too large, and it is difficult to form a uniform coating on the surface of the aerogel. In addition, PBO fibers can be dispersed in two acids, methanesulfonic acid and trifluoroacetic acid. PBO fibers disperse faster in trifluoroacetic acid, but the formed PBO nanofibers are uneven. In order to control the dispersion rate of PBO fibers in the acid solution, 100 to 300 parts of methanesulfonic acid and 100 to 300 parts of trifluoroacetic acid are distributed. The present invention uses the outstanding thermal decomposition temperature (650°C), extremely high tensile strength (5.8GPa) and excellent flame retardant performance (limiting oxygen index of 68) of PBO fibers to prepare multifunctional nanofiber aerogels. If the amount of PBO fibers used is small, the flame retardant performance of the prepared nanofiber aerogels may decrease.
[0027] The second technical solution of the present invention is a method for preparing the above-mentioned double cross-linked network structure PBO composite aerogel, comprising the following steps: immersing the nanocomposite aerogel in a mixed solution of fluorocarbon resin and fumed silica to obtain the double cross-linked network structure PBO composite aerogel.
[0028] Preferably, the method for preparing the nanocomposite aerogel comprises the following steps:
[0029] The PBO fibers are dispersed in a mixed acid solution consisting of methanesulfonic acid and trifluoroacetic acid to obtain a PBO nanofiber dispersion;
[0030] Adding benzoxazine and anhydrous sodium sulfate into the PBO nanofiber dispersion to prepare a polybenzoxazine / PBO nanocomposite acid sol;
[0031] The polybenzoxazine / PBO nanocomposite acid gel is subjected to solvent exchange in a solvent and then freeze-dried to obtain the nanocomposite aerogel.
[0032] Preferably, the step of adding benzoxazine and anhydrous sodium sulfate to the PBO nanofiber dispersion to prepare the polybenzoxazine / PBO nanocomposite acid sol specifically comprises: adding benzoxazine and anhydrous sodium sulfate to the PBO nanofiber dispersion, stirring at high speed, and standing to obtain the polybenzoxazine / PBO nanocomposite acid sol.
[0033] Preferably, the high-speed stirring speed is 10,000 to 18,000 rpm, and the time is 20 to 60 minutes.
[0034] Preferably, the standing is at 20-25° C. for 10-30 hours.
[0035] Preferably, the solvent used in the solvent exchange is deionized water.
[0036] Compared with other solvents, deionized water has a faster exchange rate as an exchange solvent and will not damage the nanofiber gel structure. At the same time, using deionized water as an exchange solvent can directly carry out the freeze-drying process, reducing the requirements for equipment. In addition, other organic solvents may cause a certain degree of damage to the structure of PBO nanofibers and polybenzoxazine.
[0037] Preferably, the solvent exchange time is 2 to 4 hours.
[0038] Preferably, the solvent is exchanged 6 to 10 times.
[0039] Preferably, the freeze-drying temperature is -80 to -60°C.
[0040] Preferably, the freeze-drying time is 30 to 72 hours.
[0041] Preferably, the dispersion is achieved by stirring, the stirring speed is 500 to 1000 rpm, and the stirring time is 48 to 96 hours.
[0042] Preferably, in the mixed acid solution, the mass ratio of methanesulfonic acid to trifluoroacetic acid is 1-2:0.5-1.5.
[0043] Preferably, the mass ratio of the PBO fiber to the mixed acid solution is 10-50:100-300.
[0044] Preferably, the mass ratio of the PBO fiber to benzoxazine is 1-5:5-10.
[0045] Preferably, the mass ratio of the PBO fiber to anhydrous sodium sulfate is 10-50:2-5.
[0046] Preferably, the mass ratio of the fluorocarbon resin to the fumed silica is 80-140:1-4.
[0047] Preferably, the soaking time is 5 to 30 minutes.
[0048] Preferably, the method for preparing the double cross-linked network structure PBO composite aerogel comprises the following steps:
[0049] (1) Put an appropriate amount of PBO fibers into a methanesulfonic acid / trifluoroacetic acid mixed acid and obtain a PBO nanofiber dispersion after magnetic stirring;
[0050] (2) adding benzoxazine and anhydrous sodium sulfate to the PBO nanofiber dispersion, stirring with a high-speed homogenizer to obtain a polybenzoxazine / PBO nanocomposite acid sol, and standing at room temperature to obtain a polybenzoxazine / PBO nanocomposite acid gel;
[0051] (3) immersing the polybenzoxazine / PBO nanocomposite acid gel in deionized water for solvent exchange to obtain a nanocomposite hydrogel, and freeze-drying to obtain a polybenzoxazine / PBO nanocomposite aerogel;
[0052] (4) The polybenzoxazine / PBO nanocomposite aerogel is immersed in a fluorocarbon resin / fumed silica solution, and then taken out and dried to obtain a double cross-linked network structure PBO composite aerogel.
[0053] The present invention first puts an appropriate amount of PBO fiber into a methanesulfonic acid / trifluoroacetic acid mixed acid, and obtains a PBO nanofiber dispersion after magnetic stirring; then benzoxazine and anhydrous sodium sulfate are added to the PBO nanofiber dispersion, and a polybenzoxazine / PBO nanocomposite acid sol is obtained by stirring with a high-speed homogenizer, and a polybenzoxazine / PBO nanocomposite acid gel is obtained by standing at room temperature; then the polybenzoxazine / PBO nanocomposite acid gel is immersed in deionized water for solvent exchange to obtain a nanocomposite hydrogel, and a polybenzoxazine / PBO nanocomposite aerogel is obtained by freeze drying; finally, the polybenzoxazine / PBO nanocomposite aerogel is immersed in a fluorocarbon resin / fumed silica solution, and then a double cross-linked network structure PBO composite aerogel is obtained, and a layer of super-hydrophobic coating is deposited on the surface of the nanocomposite aerogel by regulating the ratio of fluorocarbon resin and fumed silica. The preparation method provided by the present invention is simple to operate, suitable for industrial batch production, and the obtained nanocomposite aerogel is expected to be applied to some extreme environments.
[0054] The extreme environment described in the present invention refers to an environment at a relatively high temperature. For example, as an aerospace material, when the aircraft returns, friction with the atmosphere generates a high-temperature environment. The thermal decomposition temperature of the PBO fiber of the present invention can reach 650°C, which is much higher than the heat-resistant temperature (300°C) of conventional polymer aerogels. Therefore, PBO composite aerogel has a good application prospect in the field of thermal insulation layer of spacecraft.
[0055] The present invention adds anhydrous sodium sulfate to the pre-prepared PBO nanofiber dispersion, and the sulfate ions of the anhydrous sodium sulfate combine with the hydrogen ions of the PBO molecular chain, thereby reducing the electrostatic repulsion between the PBO molecular chains, improving the interaction between the PBO molecular chains, and forming stable PBO nanofibers. The order in which the anhydrous sodium sulfate and benzoxazine are added to the PBO nanofiber dispersion does not affect the modification effect.
[0056] The present invention uses methanesulfonic acid / trifluoroacetic acid mixed acid to prepare PBO nanofiber dispersion liquid, and by adjusting the ratio of methanesulfonic acid and trifluoroacetic acid, the PBO molecular chains are better dispersed in the acid solution, so as to subsequently form PBO nanofibers.
[0057] A third technical solution of the present invention is the use of the above-mentioned double-crosslinked network structure PBO composite aerogel as a thermal insulation material.
[0058] Optionally, the double-crosslinked network structure PBO composite aerogel can be used in thermal insulation layers in the aerospace field or thermal insulation materials in the construction field.
[0059] The present invention discloses the following technical effects:
[0060] The double cross-linked network structure PBO composite aerogel provided by the present invention has super hydrophobicity, excellent flame retardant properties, high mechanical properties and low thermal conductivity, and its compression strength is 1.24-1.53MPa, the contact angle with water is 142.1-152.3°, the combustion grade is UL94 V-0, and the thermal conductivity is 0.034-0.038W / (m·K). It has broad application prospects in aerospace, electronic information, transportation, transportation, electronic and electrical fields, and 5G communications. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0062] Figure 1 This is an infrared spectrum analysis diagram of benzoxazine, PBO nanofiber and polybenzoxazine / PBO nanocomposite aerogel in Experimental Example 2 of the present invention;
[0063] Figure 2 The SEM images of the PBO composite aerogel and the double cross-linked network structure PBO composite aerogel in Experimental Example 2 of the present invention;
[0064] Figure 3The contact angles of the polybenzoxazine / PBO nanocomposite aerogel and the double cross-linked network structure PBO composite aerogel with water in Experimental Example 2 of the present invention;
[0065] Figure 4 A schematic diagram of preparing a double cross-linked network structure PBO composite aerogel according to the present invention;
[0066] Figure 5 This is a reaction process diagram of obtaining polybenzoxazine by acid catalysis of benzoxazine used in an embodiment of the present invention. DETAILED DESCRIPTION
[0067] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0068] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0069] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0070] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0071] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0072] The present invention provides a double cross-linked network structure PBO composite aerogel, and its raw material components include, by weight:
[0073]
[0074] In terms of mass fraction, the raw material of the double cross-linked network structure PBO composite aerogel provided by the present invention preferably includes 10 to 50 parts of PBO fibers, preferably 20 to 50 parts, and most preferably 40 parts. In the present invention, the length of the PBO fibers is preferably 10 to 20 cm, and the diameter is preferably 10 to 15 μm. In the present invention, the source of the PBO fibers is preferably commercially available.
[0075] In terms of mass fraction, the raw material of the double cross-linked network structure PBO composite aerogel provided by the present invention preferably includes 100 to 300 parts of methanesulfonic acid, preferably 100 to 200 parts, and most preferably 150 parts. In the present invention, the source of the methanesulfonic acid is preferably commercially available.
[0076] In terms of mass fraction, the raw material of the double cross-linked network structure PBO composite aerogel provided by the present invention preferably includes 100 to 300 parts of trifluoroacetic acid, preferably 100 to 200 parts, and most preferably 150 parts. In the present invention, the source of the trifluoroacetic acid is preferably commercially available.
[0077] Based on the mass fraction of the PBO fiber, the raw materials of the double cross-linked network structure PBO composite aerogel provided by the present invention preferably include 50 to 100 parts of benzoxazine, more preferably 70 to 100 parts, and most preferably 80 parts. In the present invention, the source of the benzoxazine is preferably commercially available, and the purity is preferably ≥95%. In the present invention, the benzoxazine is spontaneously polymerized and cross-linked in the PBO nanofiber network under the catalysis of trifluoroacetic acid and methanesulfonic acid, thereby forming a stable double network aerogel structure.
[0078] Based on the mass fraction of the PBO fiber, the raw material of the double cross-linked network structure PBO composite aerogel provided by the present invention preferably includes 2 to 5 parts of anhydrous sodium sulfate, more preferably 3 to 5 parts, and most preferably 3 parts. In the present invention, the source of the anhydrous sodium sulfate is preferably commercially available, and the purity is preferably ≥95%.
[0079] Based on the mass fraction of the PBO fiber, the raw material of the double cross-linked network structure PBO composite aerogel provided by the present invention preferably includes 2 to 5 parts of anhydrous sodium sulfate, more preferably 3 to 5 parts, and most preferably 3 parts. In the present invention, the source of the anhydrous sodium sulfate is preferably commercially available, and the purity is preferably ≥95%.
[0080] Based on the mass fraction of the PBO fiber, the raw material of the double cross-linked network structure PBO composite aerogel provided by the present invention preferably includes 80 to 140 parts of fluorocarbon resin, more preferably 80 to 120 parts, and most preferably 80 parts. In the present invention, the source of the fluorocarbon resin is preferably commercially available.
[0081] Based on the mass fraction of the PBO fiber, the raw material of the double cross-linked network structure PBO composite aerogel provided by the present invention preferably includes 1 to 4 parts of fumed silica, more preferably 1 to 3 parts, and most preferably 2 parts. In the present invention, the source of the fumed silica is preferably commercially available.
[0082] In the present invention, the fluorocarbon resin and aerosilicic acid have excellent hydrophobicity, and can impart super-hydrophobic properties to the nanocomposite aerogel by simple soaking and drying.
[0083] The present invention provides a method for preparing the above-mentioned double-crosslinked network structure PBO composite aerogel, comprising the following steps:
[0084] (1) Put an appropriate amount of PBO fibers into a methanesulfonic acid / trifluoroacetic acid mixed acid and obtain a PBO nanofiber dispersion after magnetic stirring;
[0085] (2) adding benzoxazine and anhydrous sodium sulfate to the PBO nanofiber dispersion, stirring with a high-speed homogenizer to obtain a polybenzoxazine / PBO nanocomposite acid sol, and standing at room temperature to obtain a polybenzoxazine / PBO nanocomposite acid gel;
[0086] (3) immersing the polybenzoxazine / PBO nanocomposite acid gel in deionized water for solvent exchange to obtain a nanocomposite hydrogel, and freeze-drying to obtain a polybenzoxazine / PBO nanocomposite aerogel;
[0087] (4) The polybenzoxazine / PBO nanocomposite aerogel is immersed in a fluorocarbon resin / fumed silica solution, and then taken out and dried to obtain a double cross-linked network structure PBO composite aerogel.
[0088] In the present invention, the solvent of the acid dispersion of the PBO fiber is a mixed acid of methanesulfonic acid and trifluoroacetic acid. In the present invention, the mass concentration of the methanesulfonic acid is preferably ≥99%, and the mass concentration of the trifluoroacetic acid is preferably ≥99%. In the present invention, the mass ratio of methanesulfonic acid to trifluoroacetic acid in the mixed acid is preferably 1-2:0.5-1.5, more preferably 1:1. The magnetic stirring time is preferably 48-96 hours, more preferably 72 hours.
[0089] Methanesulfonic acid and trifluoroacetic acid are both strong acidic solvents that can provide a protonated environment, generating hydrogen bonds and charge interactions on electron-rich atoms such as nitrogen and oxygen in PBO molecules. Since PBO has high rigidity and strong π-π stacking between molecules, it is difficult for ordinary solvents to disperse it, and the strong acidic environment of methanesulfonic acid and trifluoroacetic acid helps to destroy the interaction between PBO molecules.
[0090] In the present invention, the magnetic stirring rate is preferably 500-1000 rpm, more preferably 800 rpm. In the present invention, during the stirring and mixing process, the PBO fibers are dissolved in the mixed acid to form a stable PBO nanofiber dispersion.
[0091] In the present invention, in the PBO fiber dispersion, the mass ratio of the PBO fiber to the methanesulfonic acid / trifluoroacetic acid mixed acid is 10-50:100-300, more preferably 40:300.
[0092] In the present invention, the mass ratio of the added benzoxazine and anhydrous sodium sulfate, PBO fiber to benzoxazine is preferably 1-5:5-10, more preferably 4:8; the mass ratio of PBO fiber to anhydrous sodium sulfate is 10-50:2-5, preferably 40:3.
[0093] In the present invention, the high-speed homogenizing stirring time is preferably 20 to 60 minutes, more preferably 40 minutes; the rotation speed is 10,000 to 18,000 rpm, more preferably 15,000 rpm, so that the PBO nanofibers, benzoxazine and anhydrous sodium sulfate are evenly mixed.
[0094] In the present invention, the room temperature standing time is preferably 10 to 30 hours, more preferably 24 hours.
[0095] In the present invention, the solvent exchange is performed by exchanging the mixed acid with distilled water, so that the excess acid in the PBO nanofiber acid gel can be removed for the next freeze drying. Therefore, the number of solvent exchanges is based on the neutrality of the solution. The solvent exchange process time is preferably 2 to 4 hours, more preferably 3 hours; the number of solvent exchanges is preferably 6 to 10 times, more preferably 8 times.
[0096] In the present invention, the freeze-drying process is completed in a vacuum freeze dryer, and the temperature setting is preferably -80 to -60°C, more preferably -80°C; the equipment operation time is preferably 30 to 72 hours, more preferably 48 hours.
[0097] In the present invention, the mass ratio of fluorocarbon resin to fumed silica in the fluorocarbon resin / fumed silica solution is preferably 80-140:1-4, more preferably 80:2; the immersion time is preferably 5-30 minutes, more preferably 10 minutes.
[0098] The present invention introduces benzoxazine into a poly(p-phenylene benzobisoxazole) (PBO) nanofiber dispersion, and further prepares a double-network structure polybenzoxazine / PBO nanocomposite aerogel by a sol-gel method. Then, the benzoxazine / PBO nanocomposite aerogel is immersed in a fluorocarbon resin / fumed silica solution, and then taken out and dried to obtain a double-crosslinked network structure PBO composite aerogel. The present invention uses trifluoroacetic acid and methanesulfonic acid as acid catalysts to promote the ring-opening polymerization of benzoxazine to form polybenzoxazine, thereby forming an interpenetrating network structure with PBO nanofibers to obtain a stable nanocomposite aerogel; by adjusting the ratio of fluorocarbon resin and fumed silica, a super-hydrophobic coating is deposited on the surface of the nanocomposite aerogel to make it exhibit super-hydrophobic properties.
[0099] The following is a detailed description of a double cross-linked network structure PBO composite aerogel and a preparation method thereof provided by the present invention in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0100] The embodiment of the present invention does not limit the mass level of the material usage, as long as the required raw materials are added according to the mass fraction.
[0101] The structural formula of the benzoxazine used in the embodiment of the present invention is as follows. The reaction process of obtaining polybenzoxazine by acid catalysis of the benzoxazine is as follows: Figure 5 As shown:
[0102]
[0103] Other diamine / phenol-type benzoxazines (such as the following structural formula) can also be used to prepare the double-crosslinked network structure PBO composite aerogel of the present invention without affecting the final technical effect.
[0104]
[0105] The room temperature condition in the embodiments of the present invention is: 20-25°C.
[0106] The fluorocarbon resin used in the embodiment of the present invention is specifically the fluorinated liquid of Shenzhen Zhongfu Technology Co., Ltd., model number Fluere 1706.
[0107] Example 1
[0108] 30 parts by weight of PBO fibers were placed in 300 parts by weight of a mixed acid of methanesulfonic acid / trifluoroacetic acid (mass ratio of 1:1), and magnetic stirring was applied for 72 hours to dissolve the PBO fibers in the mixed acid to obtain a stable PBO nanofiber dispersion. Methanesulfonic acid and trifluoroacetic acid are both strong acidic solvents that can provide a protonated environment, generating hydrogen bonding and charge interactions on electron-rich atoms such as nitrogen and oxygen in PBO molecules. Since PBO has high rigidity and strong π-π stacking between molecules, it is difficult for ordinary solvents to disperse it, and the strong acidic environment of methanesulfonic acid and trifluoroacetic acid helps to destroy the interactions between PBO molecules.
[0109] 3 parts by weight of anhydrous sodium sulfate and 90 parts by weight of benzoxazine were added to the PBO nanofiber dispersion, and stirred for 40 minutes by a high-speed homogenizer (15,000 rpm) to obtain a polybenzoxazine / PBO nanocomposite acid sol. Then, the polybenzoxazine / PBO nanocomposite acid sol was poured into a beaker and allowed to stand at room temperature for 24 hours to obtain a polybenzoxazine / PBO nanocomposite acid gel.
[0110] The acid gel was then immersed in deionized water for solvent exchange to obtain the polybenzoxazine / PBO nanocomposite hydrogel. The solvent exchange time was 3 hours and the number of solvent exchanges was 8 times.
[0111] Then, the polybenzoxazine / PBO nanocomposite hydrogel was freeze-dried to obtain the polybenzoxazine / PBO nanocomposite aerogel, the freeze-drying temperature was set to -80°C, and the freeze-drying time was set to 48 hours.
[0112] Subsequently, 80 parts by weight of fluorocarbon resin and 2 parts by weight of fumed silica were prepared into a mixed solution, and the polybenzoxazine / PBO nanocomposite aerogel was immersed in the solution for 10 minutes, and then taken out and dried to obtain a double cross-linked network structure PBO composite aerogel.
[0113] Example 2
[0114] 40 parts by weight of PBO fibers were placed in 300 parts by weight of a mixed acid of methanesulfonic acid / trifluoroacetic acid with a mass ratio of 0.5:1.3, and magnetic stirring was performed for 96 hours to obtain a PBO nanofiber dispersion. Methanesulfonic acid and trifluoroacetic acid are both strong acidic solvents that can provide a protonation environment, generating hydrogen bonding and charge interactions on electron-rich atoms such as nitrogen and oxygen in PBO molecules. Since PBO has high rigidity and strong π-π stacking between molecules, it is difficult to disperse it with ordinary solvents, and the strong acidic environment of methanesulfonic acid and trifluoroacetic acid helps to destroy the interactions between PBO molecules.
[0115] 4 parts by weight of anhydrous sodium sulfate and 80 parts by weight of benzoxazine were added to the PBO nanofiber dispersion, and stirred for 30 minutes by a high-speed homogenizer (12000 rpm) to obtain a polybenzoxazine / PBO nanocomposite acid sol. Then, the polybenzoxazine / PBO nanocomposite acid sol was poured into a beaker and allowed to stand at room temperature for 15 hours to obtain a polybenzoxazine / PBO nanocomposite acid gel. The acid gel was then immersed in deionized water for solvent exchange to obtain a polybenzoxazine / PBO nanocomposite hydrogel, the solvent exchange time was 2 hours, and the solvent exchange number was 6 times.
[0116] Then, the polybenzoxazine / PBO nanocomposite hydrogel was freeze-dried to obtain a polybenzoxazine / PBO nanocomposite aerogel, the freeze-drying temperature was set to -60°C, and the freeze-drying time was set to 30 hours. Subsequently, 140 parts by weight of fluorocarbon resin and 1 part by weight of fumed silica were prepared into a mixed solution, and the polybenzoxazine / PBO nanocomposite aerogel was immersed in the above solution for 5 minutes, and then taken out and dried to obtain a double cross-linked network structure PBO composite aerogel.
[0117] Example 3
[0118] 20 parts by weight of PBO fibers were placed in 200 parts by weight of a mixed acid of methanesulfonic acid / trifluoroacetic acid with a mass ratio of 1.8:1.2, and magnetic stirring was performed for 96 hours to obtain a PBO nanofiber dispersion. Methanesulfonic acid and trifluoroacetic acid are both strong acidic solvents that can provide a protonation environment, generating hydrogen bonding and charge interactions on electron-rich atoms such as nitrogen and oxygen in PBO molecules. Since PBO has high rigidity and strong π-π stacking between molecules, it is difficult to disperse it with ordinary solvents, and the strong acidic environment of methanesulfonic acid and trifluoroacetic acid helps to destroy the interactions between PBO molecules.
[0119] 5 parts by weight of anhydrous sodium sulfate and 80 parts by weight of benzoxazine were added to the PBO nanofiber dispersion, and the mixture was stirred for 50 minutes by a high-speed homogenizer (18,000 rpm) to obtain a polybenzoxazine / PBO nanocomposite acid sol. Then, the polybenzoxazine / PBO nanocomposite acid sol was poured into a beaker and allowed to stand at room temperature for 30 hours to obtain a polybenzoxazine / PBO nanocomposite acid gel. The acid gel was then immersed in deionized water for solvent exchange to obtain a polybenzoxazine / PBO nanocomposite hydrogel, the solvent exchange time was 4 hours, and the solvent exchange number was 10 times.
[0120] Then, the polybenzoxazine / PBO nanocomposite hydrogel was freeze-dried to obtain a polybenzoxazine / PBO nanocomposite aerogel, the freeze-drying temperature was set to -80°C, and the freeze-drying time was set to 72 hours. Subsequently, 80 parts by weight of fluorocarbon resin and 4 parts by weight of fumed silica were prepared into a mixed solution, and the polybenzoxazine / PBO nanocomposite aerogel was immersed in the above solution for 30 minutes, and then taken out and dried to obtain a double cross-linked network structure PBO composite aerogel.
[0121] Embodiment 4-6
[0122] Same as Example 1, except that the raw material ratios are different, as shown in Table 1.
[0123] Table 1
[0124] Example 4 Example 5 Example 6 PBO fiber 50 servings 30 servings 40 servings Methanesulfonic acid 300 copies 100 copies 200 copies Trifluoroacetic acid 100 copies 300 copies 200 copies Benzoxazine 50 servings 80 servings 70 servings Anhydrous sodium sulfate 3 servings 4 servings 5 servings Fluorocarbon resin 130 copies 120 servings 80 servings Fumed Silica 1 serving 4 servings 2 servings
[0125] Comparative Example 1
[0126] A PBO composite aerogel was prepared according to the method of Example 1, except that anhydrous sodium sulfate and benzoxazine were not added, as follows:
[0127] 30 parts by weight of PBO fiber were placed in 300 parts by weight of a mixed acid of methanesulfonic acid / trifluoroacetic acid with a mass ratio of 1:1, and magnetically stirred for 72 hours to obtain a PBO nanofiber dispersion, which was stirred for 40 minutes by a high-speed homogenizer (15,000 rpm) to obtain a PBO nanocomposite acid sol. Then, the PBO nanocomposite acid sol was poured into a beaker and allowed to stand at room temperature for 24 hours to obtain a PBO nanocomposite acid gel. The acid gel was then immersed in deionized water for solvent exchange to obtain a PBO nanocomposite hydrogel, the solvent exchange time was 3 hours, and the solvent exchange number was 8 times.
[0128] Then, the PBO nanocomposite hydrogel was freeze-dried to obtain a PBO nanocomposite aerogel, the freeze-drying temperature was set to -80°C, and the freeze-drying time was set to 48 hours. Subsequently, 80 parts by weight of fluorocarbon resin and 2 parts by weight of fumed silica were prepared into a mixed solution, and the PBO nanocomposite aerogel was immersed in the solution for 10 minutes, and then taken out and dried to obtain the PBO composite aerogel.
[0129] Comparative Example 2
[0130] The polybenzoxazine / PBO nanocomposite aerogel was prepared according to the method of Example 1, except that no fluorocarbon resin and fumed silica were added, as follows:
[0131] 30 parts by weight of PBO fibers were added into 300 parts by weight of a 1:1 methanesulfonic acid / trifluoroacetic acid mixed acid, and magnetically stirred for 72 hours to obtain a PBO nanofiber dispersion.
[0132] 3 parts by weight of anhydrous sodium sulfate and 90 parts by weight of benzoxazine were added to the PBO nanofiber dispersion, and stirred for 40 minutes by a high-speed homogenizer (15,000 revolutions). Then, the polybenzoxazine / PBO nanocomposite acid sol was poured into a beaker and allowed to stand at room temperature for 24 hours to obtain a polybenzoxazine / PBO nanocomposite acid gel. The acid gel was then immersed in deionized water for solvent exchange to obtain a polybenzoxazine / PBO nanocomposite hydrogel, the solvent exchange time was 3 hours, and the solvent exchange number was 8 times.
[0133] Then, the polybenzoxazine / PBO nanocomposite hydrogel was freeze-dried to obtain the polybenzoxazine / PBO nanocomposite aerogel, the freeze-drying temperature was set to -80°C, and the freeze-drying time was set to 48 hours.
[0134] Comparative Example 3
[0135] A double cross-linked network structure PBO composite aerogel was prepared according to the method of Example 1, except that anhydrous sodium sulfate was not added, as follows:
[0136] 30 parts by weight of PBO fibers were added into 300 parts by weight of a 1:1 methanesulfonic acid / trifluoroacetic acid mixed acid, and magnetically stirred for 72 hours to obtain a PBO nanofiber dispersion.
[0137] 90 parts by weight of benzoxazine was added to the PBO nanofiber dispersion, and the mixture was stirred for 40 minutes by a high-speed homogenizer (15,000 rpm) to obtain a polybenzoxazine / PBO nanocomposite acid sol. Then, the polybenzoxazine / PBO nanocomposite acid sol was poured into a beaker and allowed to stand at room temperature for 24 hours to obtain a polybenzoxazine / PBO nanocomposite acid gel.
[0138] The acid gel was then immersed in deionized water for solvent exchange to obtain the polybenzoxazine / PBO nanocomposite hydrogel. The solvent exchange time was 3 hours and the number of solvent exchanges was 8 times.
[0139] Then, the polybenzoxazine / PBO nanocomposite hydrogel was freeze-dried to obtain the polybenzoxazine / PBO nanocomposite aerogel, the freeze-drying temperature was set to -80°C, and the freeze-drying time was set to 48 hours.
[0140] Subsequently, 80 parts by weight of fluorocarbon resin and 2 parts by weight of fumed silica were prepared into a mixed solution, and the polybenzoxazine / PBO nanocomposite aerogel was immersed in the solution for 10 minutes, and then taken out and dried to obtain a double cross-linked network structure PBO composite aerogel.
[0141] Comparative Example 4
[0142] A double cross-linked network structure PBO composite aerogel was prepared according to the method of Example 1, except that fumed silica was not added and 82 parts of fluorocarbon resin were used; the details are as follows:
[0143] 30 parts by weight of PBO fibers were added into 300 parts by weight of a 1:1 methanesulfonic acid / trifluoroacetic acid mixed acid, and magnetically stirred for 72 hours to obtain a PBO nanofiber dispersion.
[0144] 3 parts by weight of anhydrous sodium sulfate and 90 parts by weight of benzoxazine were added to the PBO nanofiber dispersion, and stirred for 40 minutes by a high-speed homogenizer (15,000 rpm) to obtain a polybenzoxazine / PBO nanocomposite acid sol. Then, the polybenzoxazine / PBO nanocomposite acid sol was poured into a beaker and allowed to stand at room temperature for 24 hours to obtain a polybenzoxazine / PBO nanocomposite acid gel.
[0145] The acid gel was then immersed in deionized water for solvent exchange to obtain the polybenzoxazine / PBO nanocomposite hydrogel. The solvent exchange time was 3 hours and the number of solvent exchanges was 8 times.
[0146] Then, the polybenzoxazine / PBO nanocomposite hydrogel was freeze-dried to obtain the polybenzoxazine / PBO nanocomposite aerogel, the freeze-drying temperature was set to -80°C, and the freeze-drying time was set to 48 hours.
[0147] Subsequently, 82 parts by weight of fluorocarbon resin was prepared into a mixed solution, and the polybenzoxazine / PBO nanocomposite aerogel was immersed in the solution for 10 minutes, and then taken out and dried to obtain a double cross-linked network structure PBO composite aerogel.
[0148] Comparative Example 5
[0149] A double cross-linked network structure PBO composite aerogel was prepared according to the method of Example 1, except that trifluoroacetic acid was used to replace the methanesulfonic acid / trifluoroacetic acid mixed acid, that is, only trifluoroacetic acid was used as the acid catalyst; the details are as follows:
[0150] 30 parts by weight of PBO fibers were added to 300 parts by weight of trifluoroacetic acid and stirred magnetically for 72 hours to obtain a PBO nanofiber dispersion.
[0151] 3 parts by weight of anhydrous sodium sulfate and 90 parts by weight of benzoxazine were added to the PBO nanofiber dispersion, and stirred for 40 minutes by a high-speed homogenizer (15,000 rpm) to obtain a polybenzoxazine / PBO nanocomposite acid sol. Then, the polybenzoxazine / PBO nanocomposite acid sol was poured into a beaker and allowed to stand at room temperature for 24 hours to obtain a polybenzoxazine / PBO nanocomposite acid gel.
[0152] The acid gel was then immersed in deionized water for solvent exchange to obtain the polybenzoxazine / PBO nanocomposite hydrogel. The solvent exchange time was 3 hours and the number of solvent exchanges was 8 times.
[0153] Then, the polybenzoxazine / PBO nanocomposite hydrogel was freeze-dried to obtain the polybenzoxazine / PBO nanocomposite aerogel, the freeze-drying temperature was set to -80°C, and the freeze-drying time was set to 48 hours.
[0154] Subsequently, 80 parts by weight of fluorocarbon resin and 2 parts by weight of fumed silica were prepared into a mixed solution, and the polybenzoxazine / PBO nanocomposite aerogel was immersed in the solution for 10 minutes, and then taken out and dried to obtain a double cross-linked network structure PBO composite aerogel.
[0155] Comparative Example 6
[0156] A double cross-linked network structure PBO composite aerogel was prepared according to the method of Example 1, except that methanesulfonic acid was used to replace the methanesulfonic acid / trifluoroacetic acid mixed acid, that is, only methanesulfonic acid was used as the acid catalyst; the details are as follows:
[0157] 30 parts by weight of PBO fibers were added to 300 parts by weight of methanesulfonic acid and stirred magnetically for 72 hours to obtain a PBO nanofiber dispersion.
[0158] 3 parts by weight of anhydrous sodium sulfate and 90 parts by weight of benzoxazine were added to the PBO nanofiber dispersion, and stirred for 40 minutes by a high-speed homogenizer (15,000 rpm) to obtain a polybenzoxazine / PBO nanocomposite acid sol. Then, the polybenzoxazine / PBO nanocomposite acid sol was poured into a beaker and allowed to stand at room temperature for 24 hours to obtain a polybenzoxazine / PBO nanocomposite acid gel.
[0159] The acid gel was then immersed in deionized water for solvent exchange to obtain the polybenzoxazine / PBO nanocomposite hydrogel. The solvent exchange time was 3 hours and the number of solvent exchanges was 8 times.
[0160] Then, the polybenzoxazine / PBO nanocomposite hydrogel was freeze-dried to obtain the polybenzoxazine / PBO nanocomposite aerogel, the freeze-drying temperature was set to -80°C, and the freeze-drying time was set to 48 hours.
[0161] Subsequently, 80 parts by weight of fluorocarbon resin and 2 parts by weight of fumed silica were prepared into a mixed solution, and the polybenzoxazine / PBO nanocomposite aerogel was immersed in the solution for 10 minutes, and then taken out and dried to obtain a double cross-linked network structure PBO composite aerogel.
[0162] Comparative Example 7
[0163] A PBO composite aerogel was prepared according to the method of Example 1, except that silicon dioxide was used instead of benzoxazine; the details are as follows:
[0164] 30 parts by weight of PBO fibers were added to 300 parts by weight of a mixed acid of methanesulfonic acid / trifluoroacetic acid (mass ratio of 1:1), and magnetic stirring was performed for 72 hours to obtain a PBO nanofiber dispersion.
[0165] 3 parts by weight of anhydrous sodium sulfate and 90 parts by weight of silicon dioxide were added to the PBO nanofiber dispersion, and stirred for 40 minutes by a high-speed homogenizer (15,000 rpm) to obtain a silicon dioxide / PBO nanocomposite acid sol. Then, the silicon dioxide / PBO nanocomposite acid sol was poured into a beaker and allowed to stand at room temperature for 24 hours to obtain a silicon dioxide / PBO nanocomposite acid gel.
[0166] The acid gel was then immersed in deionized water for solvent exchange to obtain a silica / PBO nanocomposite hydrogel. The solvent exchange time was 3 hours and the number of solvent exchanges was 8 times.
[0167] Then, the silica / PBO nanocomposite hydrogel was freeze-dried to obtain the silica / PBO nanocomposite aerogel, the freeze-drying temperature was set to -80°C, and the freeze-drying time was set to 48 hours.
[0168] Subsequently, 80 parts by weight of fluorocarbon resin and 2 parts by weight of fumed silica were prepared into a mixed solution, and the silica / PBO nanocomposite aerogel was immersed in the solution for 10 minutes, and then taken out and dried to obtain the PBO composite aerogel.
[0169] Test Example 1
[0170] The products prepared in the above examples and comparative examples were subjected to performance tests, and the test results are listed in Table 2. The test method is as follows:
[0171] (1) Compression strength: The compressive strength of the specimens was tested using a mechanical testing machine in accordance with ISO 844:2014. If the total strain was >10%, the stress at 10% deformation was taken as the yield stress (compressive strength); if the total strain was <10%, the maximum yield stress was taken.
[0172] (2) Flame retardant test: Vertical burning test (UL94) was carried out on FTT0082 instrument in accordance with GB / T 8333-2008.
[0173] (3) Contact angle test: According to ASTM D5725, the contact angle between aerogel and water was recorded using a contact angle meter (JY-82B Kruss DSA, Germany).
[0174] (4) Density: The density of aerogel is calculated by volume and mass by processing the sample into a standard cylinder.
[0175] (5) Thermal conductivity: The thermal conductivity of aerogel is tested by a Hot disk thermal conductivity tester.
[0176] (6) Porosity: The porosity (P) of aerogel is calculated by the mass volume method. The calculation formula is:
[0177]
[0178] Where P is the porosity of the sample; ρ is the density of anhydrous ethanol; V is the volume of the aerogel; W 1 is the mass of aerogel; W 2 is the mass of aerogel and anhydrous ethanol.
[0179] Table 2
[0180]
[0181] It can be seen from the performance data in Table 2 that the present invention effectively improves the mechanical properties of PBO composite aerogel by introducing benzoxazine and PBO nanofibers to form a double cross-linked network structure; and effectively improves the hydrophobicity of PBO composite aerogel by introducing fluorocarbon resin and fumed silica. It can be seen from the comparative example that the PBO composite aerogel without the addition of benzoxazine or fluorocarbon resin / fumed silica has low mechanical strength or hydrophobicity, which is difficult to meet the practical application of engineering. In addition, the aerogel with a double cross-linked network structure has a lower density and thermal conductivity and a higher porosity. Compared with the embodiment, if trifluoroacetic acid or methanesulfonic acid is used alone as an acid solvent, its dispersibility effect on PBO nanowires is not good, and its mechanical properties, density, thermal conductivity and porosity are still a certain distance from the embodiment. In general, a double cross-linked network structure PBO composite aerogel prepared by the present invention has broad application prospects in the fields of aerospace, transportation, and electronics.
[0182] Test Example 2
[0183] (1) The benzoxazine, PBO nanofibers and polybenzoxazine / PBO nanocomposite aerogel (benzoxazine / PBO nanofibers) in Example 1 were subjected to infrared spectroscopy analysis. The results are shown in Figure 1 . Figure 1 It is shown that for benzoxazine, due to the asymmetric stretching vibration of the tertiary amine, the -1 The characteristic absorption peak of benzene and o-oxazine ring is at 939cm -1 For PBO nanofibers, 1620, 1500 and 3058 cm -1The nearby bands correspond to the stretching vibration peaks of C=C, CC and CH of the benzene ring. In addition, the vibration peak of the oxazole ring appears at 1628 cm -1 (C=N) and 1050cm -1 After the introduction of benzoxazine into PBO nanofibers, in addition to the basic characteristic peaks of PNF and BOZ, the peak at 3400 cm -1 A new characteristic peak appeared near the oxazine ring, while the characteristic peak of the oxazine ring disappeared. This is mainly due to the opening of the oxazine ring to form -OH, proving that the ring-opening polymerization of benzoxazine and PBO nanofibers formed a double network structure.
[0184] (2) SEM analysis was performed on the PBO composite aerogel of Comparative Example 1 and the double cross-linked network structure PBO composite aerogel of Example 1. The results are shown in Figure 2 . Figure 2 The results show that the PBO composite aerogel and the double cross-linked network structure PBO composite aerogel present a mesoporous structure. The double cross-linked network structure PBO composite aerogel has a uniform porous structure, and the well-dispersed polybenzoxazine / PBO nanofibers are linked like a net to form a double cross-linked network structure. In contrast, the PBO composite aerogel without benzoxazine showed local nanofiber aggregation due to a certain degree of shrinkage.
[0185] (3) Contact angle analysis was performed on the benzoxazine / PBO nanocomposite aerogel of Comparative Example 2 (left) and the double cross-linked network structure PBO composite aerogel of Example 1 (right). The results are shown in Figure 3 . Figure 3 It is shown that compared with the PBO composite aerogel without adding fluorocarbon resin and fumed silica, the PBO composite aerogel with a double cross-linked network structure introducing fluorocarbon resin and fumed silica has excellent hydrophobicity, with a contact angle with water as high as 152.3°.
[0186] Figure 4 Schematic diagram of the preparation of the double cross-linked network structure PBO composite aerogel of the present invention ( Figure 4 In the present invention, the polybenzoxazine / PBO nanoacid gel has the same meaning as the polybenzoxazine / PBO nanocomposite acid gel described in Example 1, and the polybenzoxazine / PBO aerogel has the same meaning as the polybenzoxazine / PBO nanocomposite aerogel described in Example 1).
[0187] Figure 5 The present invention provides a route for the polymerization of benzoxazines into polybenzoxazines.
[0188] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A double cross-linked network structure PBO composite aerogel, characterized in that: The double cross-linked network structure PBO composite aerogel comprises: a nano composite aerogel with a double cross-linked network structure constructed by polybenzoxazine and PBO nanofibers, and a hydrophobic coating deposited on the surface of the nano composite aerogel; the hydrophobic coating comprises fluorocarbon resin and fumed silica.
2. The double cross-linked network structure PBO composite aerogel according to claim 1, characterized in that: Measured by weight, the raw materials of the double cross-linked network structure PBO composite aerogel include: 10 to 50 parts of PBO fibers, 100 to 300 parts of methanesulfonic acid, 100 to 300 parts of trifluoroacetic acid, 50 to 100 parts of benzoxazine, 2 to 5 parts of anhydrous sodium sulfate, 80 to 140 parts of fluorocarbon resin and 1 to 4 parts of fumed silica.
3. The double cross-linked network structure PBO composite aerogel according to claim 2, characterized in that: The mass fraction of the PBO fiber is 20 to 50 parts; and / or, The PBO fiber has a length of 10 to 20 cm and a diameter of 10 to 15 μm; and / or, The mass fraction of the methanesulfonic acid is 100 to 200 parts; and / or, The mass fraction of the trifluoroacetic acid is 100 to 200 parts; and / or, The mass fraction of the benzoxazine is 70 to 100 parts; and / or, The purity of the benzoxazine is ≥95%; and / or, The mass fraction of the anhydrous sodium sulfate is 3 to 5 parts; and / or, The purity of the anhydrous sodium sulfate is ≥95%; and / or, The mass fraction of the fluorocarbon resin is 80 to 120 parts; and / or, The mass fraction of the fumed silica is 1 to 3 parts.
4. A method for preparing a double cross-linked network structure PBO composite aerogel according to any one of claims 1 to 3, characterized in that: The following steps are involved: The nano composite aerogel is immersed in a mixed solution of fluorocarbon resin and fumed silica to obtain the double cross-linked network structure PBO composite aerogel.
5. The method for preparing the double cross-linked network structure PBO composite aerogel according to claim 4, characterized in that: The preparation method of the nanocomposite aerogel comprises the following steps: The PBO fibers are dispersed in a mixed acid solution consisting of methanesulfonic acid and trifluoroacetic acid to obtain a PBO nanofiber dispersion; Adding benzoxazine and anhydrous sodium sulfate into the PBO nanofiber dispersion to prepare a polybenzoxazine / PBO nanocomposite acid sol; The polybenzoxazine / PBO nanocomposite acid gel is subjected to solvent exchange in a solvent and then freeze-dried to obtain the nanocomposite aerogel.
6. The method for preparing the double cross-linked network structure PBO composite aerogel according to claim 5, characterized in that: The step of adding benzoxazine and anhydrous sodium sulfate to the PBO nanofiber dispersion to prepare the polybenzoxazine / PBO nanocomposite acid sol specifically comprises: adding benzoxazine and anhydrous sodium sulfate to the PBO nanofiber dispersion, stirring at high speed, and standing to obtain the polybenzoxazine / PBO nanocomposite acid sol; The high-speed stirring has a rotation speed of 10,000 to 18,000 rpm and a time of 20 to 60 minutes; and / or, The standing still step is standing still at 20-25° C. for 10-30 hours.
7. The method for preparing the double cross-linked network structure PBO composite aerogel according to claim 5, characterized in that: The solvent used in the solvent exchange is deionized water; and / or, The solvent exchange time is 2 to 4 hours; and / or, The number of solvent exchanges is 6 to 10 times; and / or, The freeze drying temperature is -80 to -60°C; and / or, The freeze-drying time is 30 to 72 hours.
8. The method for preparing the double cross-linked network structure PBO composite aerogel according to claim 5, characterized in that: The dispersion is achieved by stirring, the stirring speed is 500 to 1000 rpm, and the stirring time is 48 to 96 hours; and / or, In the mixed acid solution, the mass ratio of methanesulfonic acid to trifluoroacetic acid is 1-2:0.5-1.5; and / or, The mass ratio of the PBO fiber to the mixed acid solution is 10-50:100-300; and / or, The mass ratio of the PBO fiber to benzoxazine is 1-5:5-10; and / or, The mass ratio of the PBO fiber to anhydrous sodium sulfate is 10-50:2-5.
9. The method for preparing the double cross-linked network structure PBO composite aerogel according to claim 4, characterized in that: The mass ratio of the fluorocarbon resin to the fumed silica is 80-140:1-4; and / or, The soaking time is 5 to 30 minutes.
10. Use of the double cross-linked network structure PBO composite aerogel according to any one of claims 1 to 3 as a thermal insulation material.
Citation Information
Patent Citations
Process for preparing poly-p-phenylenebenzobisthiazole (PBO) fiber / benzoxazine composite material
CN102863634A
Polybenzoxazole nanofiber high-intensity heat insulation fireproof aerogel and preparation method thereof
CN106221216A
Preparation and application of light, heat-insulating and flame-retardant PIPD nanofiber aerogel
CN112679793A
Hydrophobic polybenzoxazine aerogel and preparation method thereof
CN118005988A